Evaluation of anticoagulant activity of aqueous extract of Cestrum nocturnum - Chandra Kishore Tyagi; Deenanath Jhade; Sunil Kumar Shah (International Journal of Phytomedicine, 2016)
The study evaluated anticoagulant properties of the aqueous extract of Cestrum nocturnum using aPTT-Activated Partial Thromboplastin Time, PT- Prothrombin Time & TT-Thrombin Time as standard procedures. For in vitro coagulation assays, aqueous extract of plant prolonged APTT, TT, and PT clotting times in a dose-dependent manner (Table 7). It prolonged APTT clotting time from 45 ± 2 (2mg/mL) to 82.2 ± 2.63s (10mg/mL), PT clotting time from 20.4 ± 1.49 (2mg/mL) to 31.4 ± 2.15s (10mg/mL), and TT clotting time from 9.2 ± 1.16 (2mg/mL) to 17.4 ± 1.01s (10mg/mL) at the concentration of 2 to 10mg/mL. Heparin prolonged APTT and PT clotting times more than 111.8s and 40.8s, respectively, at a concentration of 1 IU/mL. Heparin prolonged TT clotting times more than 20.6s at a concentration of 1 IU/mL. The phytochemical screening of the plant confirm the presence of saponin in the water and ethanolic extract, Alkaloid in all the extract except hexane extract, tannin in water, ethanol and methanol extract, amino acid in water and ethanolic extract, carbohydrate in water and methanolic extract and triterpenoids and glycoside were absent in all the extracts. The results demonstrated that the aqueous extract of Cestrum nocturnum possesses pharmacologically active anticoagulant principles that could be isolated and evaluated for clinical or physiological purposes.